THE INFLUENCE OF ADVERTISING, CELEBRITY ENDORSEMENT, BRAND AWARENESS, AND BRAND IMAGE ON PURCHASE INTENTION OF LOCAL SKINCARE PRODUCTS - Erilia Kesumahati; Febrianti Febrianti (Universitas Internasional Batam, 2022)
This study aims to determine whether there is a significant effect of celebrity endorsement, advertising, brand image and brand awareness on purchase intention on local skincare in Batam City. This study used 200 respondents using a purposive sampling method, namely only respondents who had bought local skincare in Batam City who were respondents in this study. This study uses the SPSS version 26.0 program for analysis of respondent demographic data and then continues with testing using the SmartPLS version 3.0 program for analysis of the relationship between variables. Based on the results of hypothesis testing, the data shows that celebrity endorsement, advertising, brand image and brand awareness have a significant positive effect on purchase intention. Based on the results of this study, in increasing purchase intention of local skincare, it is recommended that local skincare business actors be able to increase customer purchase interest first through the creation of good advertising, celebrity endorsement, brand awareness, and brand image.